Detection of atmospheric muon neutrinos with the IceCube 9-string detector - Achterberg, A; Ackermann, M; Adams, J; Ahrens, J; Andeen, K; Auffenberg, J; Bai, X; Baret, B; Barwick, S; Bay, R; Beattie, K; Becka, T; et al. (2007)
The IceCube neutrino detector is a cubic kilometer TeV to PeV neutrino detector under construction at the geographic South Pole. The dominant population of neutrinos detected in IceCube is due to meson decay in cosmic-ray air showers. These atmospheric neutrinos are relatively well understood and serve as a calibration and verification tool for the new detector. In 2006, the detector was approximately 10% completed, and we report on data acquired from the detector in this configuration. We observe an atmospheric neutrino signal consistent with expectations, demonstrating that the IceCube detector is capable of identifying neutrino events. In the first 137.4 days of live time, 234 neutrino candidates were selected with an expectation of 211±76.1(syst) ±14.5(stat) events from atmospheric neutrinos. © 2007 The American Physical Society.